Spectroscopy and structure of the open-shell complex O-2-N2O - Qian, H; Seccombe, D; Howard, B (1997)
The high-resolution spectrum of O2-N2O. the first for a complex containing more than one unpaired electron, has been studied in the region of the ν3 N2O monomer vibrational band using a molecular beam diode laser absorption spectrometer. The spectrum has been completely analyzed using a newly developed effective Hamiltonian. The rotational constants are accurately determined for both ground and excited vibrational states. The equilibrium structure of the complex is planar, with a separation between the centers of the mass of two monomers of 3.423 Å. The structural angles have been experimentally determined as: either θO2 = 58° and θN2O = 77°, or θO2 = 122° and θN2O = 100°. The large amplitude motion of the monomers leads to the complex having an effective out-of-plane root mean square angle of φ =φ1 - φ2 ≈ 23°. In addition, an interpretation of the structure of the complex is given in terms of an intermolecular potential using a model described by Muenter. © 1997 American Institute of Physics.